2018
DOI: 10.1080/03007995.2018.1465904
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of non-medical switch among patients with type 2 diabetes

Abstract: Approximately one in five patients reported a moderate/major negative impact on their blood glucose level, diabetes, mental well-being, general health and control over their health following a non-medical switch. Findings suggest that a non-medical switch may have unintended negative health consequences and results in considerable burden across multiple domains for a sizeable minority of patients with T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…[25][26][27][28] Furthermore, nonmedical switching is associated with worsening quality of life and worsening glycemic outcomes. 29 Though medication and supply safety issues were not identified in this study, it is possible that underground exchange activity could result in untoward health outcomes. Other research has examined how individuals assess safety related to sharing FDA approved medications.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…[25][26][27][28] Furthermore, nonmedical switching is associated with worsening quality of life and worsening glycemic outcomes. 29 Though medication and supply safety issues were not identified in this study, it is possible that underground exchange activity could result in untoward health outcomes. Other research has examined how individuals assess safety related to sharing FDA approved medications.…”
Section: Discussionmentioning
confidence: 88%
“…25-28 Furthermore, nonmedical switching is associated with worsening quality of life and worsening glycemic outcomes. 29…”
Section: Discussionmentioning
confidence: 99%
“…In all cases, the p-value used to conclude statistical significance was based on each study's defined p-value. Statistical significance was not reported for three usable endpoints from 2 studies; thus, we independently analyzed the data to estimate a p-value [12,23]. When studies reported overlapping endpoints (e.g., any hospitalization versus disease-specific hospitalization), the most disease-specific endpoint was included.…”
Section: Data Synthesismentioning
confidence: 99%
“…The initial search strategy yielded 3,177 citations and an additional 14 citations were manually identified (Figure 1). After screening and full-text assessment, 38 studies (11 studies added based on the updated search) with a total of 260,256 patients (median: 591; range: 31-102,076) and a median follow-up of 6 months (range: 0.5 to 18 months) were included in our review (Table 2) [8][9][10][11][12][13][14][15][16][17][18]. A total of 26 studies (68.4%) were published between 2000 and 2014, while 12 (31.6%) were published between 2015 and 2018.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation